2013
DOI: 10.1111/wre.12043
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence imaging: a new method for rapid detection of herbicide resistance in Alopecurus myosuroides

Abstract: Due to the steadily increasing number of putative herbicide-resistant weed populations, the demand for rapid in-season tests is rising. In this study, we introduce a new quantitative herbicide-resistance test system based on chlorophyll fluorescence imaging analysis of photosynthesis-related parameters. Susceptible and herbicide-resistant populations of Alopecurus myosuroides (black-grass) were cultivated in multiwell tissue culture plates containing nutrient agar and different dosages of fenoxaprop-P-ethyl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
(26 reference statements)
1
35
1
Order By: Relevance
“…Hence, the requirements for finding a threshold herbicide dose to discriminate between sensitive and resistant populations in a laboratory agar test were given. Kaiser et al (2013) were able to identify resistant and sensitive A. myosuroides populations within 48 h and 72 h after transplanting to fenoxaprop-Pethyl and iodosulfuron + mesosulfuron treated agar, respectively. Our preliminary studies showed that sensitive and resistant A. spica-venti populations had a difference of up to 20% in their F v /F m values 48 h and 72 h after transplanting to pinoxaden and pyroxsulam-treated agar, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the requirements for finding a threshold herbicide dose to discriminate between sensitive and resistant populations in a laboratory agar test were given. Kaiser et al (2013) were able to identify resistant and sensitive A. myosuroides populations within 48 h and 72 h after transplanting to fenoxaprop-Pethyl and iodosulfuron + mesosulfuron treated agar, respectively. Our preliminary studies showed that sensitive and resistant A. spica-venti populations had a difference of up to 20% in their F v /F m values 48 h and 72 h after transplanting to pinoxaden and pyroxsulam-treated agar, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory study. The four A. spica-venti populations were tested for herbicide sensitivity in a herbicide treated system modified according to Kaiser et al (2013). The experiments (EXP) were performed between October and December 2017.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations